CONDITION OF LEARNING RESOURCES MANAGEMENT OF PRIMARY SCHOOLS UNDER THE EDUCATION SERVICE AREA OFFICE PATHUM THANI PRIMARY SCHOOL DISTRICT 1 - Karunyawee, Supawan; Chumnisart, Booncherd; Surachayo, PhraSurachai (Journal of Educational Review Faculty of Education in MCU, 2023)
The purpose of this research was to study the condition of learning resource management of primary schools under the office of educational service areas Pathum Thani Primary School, District 1, This is mixed method research. Qualitative research by studying the document. Data were analyzed by content analysis. Quantitative research by the questionnaire with 331 samples. Data were analyzed by statistics, percentage, mean, standard deviation. Results showed that the condition of learning resource management all 3 aspects overall were at a high level, namely physical aspects, management aspects, and academic. The administrators promote teachers and personnel to have knowledge, understanding and cooperation. in the preparation of strategic plans annual action plan, use resources to operate sufficiently, economically, and cost-effectively. The administrators have guidelines, directions, and forms of organizational management, and flexibility in management organize the environment, materials, and equipment systematically to use as teaching media appropriately.